Differentiated Learning in the Merdeka Curriculum: A Literature Review on School Practices - AP, Darius; Tumonglo, Yasri Tandi; Mar’ah, Faridah Husnatul; R, Hari (Universitas Pahlawan Tuanku Tambusai, 2025)
This literature review explores the implementation of differentiated instruction within the context of Indonesia’s Merdeka Curriculum. As a major reform in the national education system, the Merdeka Curriculum promotes student-centered learning, flexibility, and autonomy in teaching. Differentiated instruction aligns closely with these goals by responding to learners’ diverse needs, interests, and readiness levels. The review synthesizes findings from national and international research to evaluate how differentiation is conceptualized, practiced, and challenged in real school settings. Key findings reveal that differentiated learning enhances student engagement, supports inclusive education, and improves academic outcomes when implemented effectively. However, it also uncovers several barriers, such as limited teacher preparedness, lack of professional development, and insufficient classroom resources. Many educators express a positive attitude toward differentiation but often struggle with its practical application due to workload, large class sizes, and curriculum constraints. The review emphasizes the need for systemic support, ongoing training, and reflective practices to ensure successful implementation. It also highlights the importance of policy alignment and school-level collaboration to cultivate a culture of differentiation. In conclusion, differentiated instruction is not just a pedagogical choice but a fundamental element in realizing the vision of Merdeka Curriculum—learning that is equitable, contextual, and meaningful for every student.